The association between competitor level and the physical preparation practices of amateur boxers. - Mitchell James Finlay; Richard Michael Page; Matt Greig; Craig Alan Bridge (PLoS ONE, 2021)
Physical training, testing, and monitoring are three key constitutes of athlete physical performance; however, there is a currently a lack of information on the prevalence of such methods in amateur boxing. This study aimed to explore the physical preparation practices of senior elite (SEB) and senior development (SDB) amateur boxers, and to determine whether these practices were discriminated by competitor level. One hundred and one amateur boxers (SEB n = 59, SDB n = 42) were surveyed on their understanding, perceptions and application of physical training, monitoring, and testing practices. SEB were associated with strength/power training (SEB 78%, SDB 50%, P = 0.005), monitor of training intensities (SEB 68%, SDB 40%, P = 0.006), and performing regular fitness testing (SEB 76%, SDB 50%, P = 0.006), compared to SDB. Likewise, SEB were twice as likely (56%) to have their physical preparation managed by a strength and conditioning (S&C) coach or sport scientist, compared to SDB (26%; P = 0.005). For the first time, these data demonstrate the extent to which competitor level is associated with preparatory practices in amateur boxing. Cost was identified as the main barrier in implementing several forms of scientific support in SDB. These data serve as a framework to enhance preparatory practices across different competitor levels in amateur boxing. This might include boxer and coach education on the benefits to a more scientific approach, and the use of cost-effective methods to develop, monitor and assess amateur boxers physical performance. This may be of particular importance where boxers are not funded, such as the SDB in the current study. However, this work may also be used to emphasise the importance of strength/power training, physical fitness testing and monitoring at the elite level of amateur boxing.